Conflicto bélico e inmunización: de la Paz de Westfalia al 11S - Garcia Matías, Bettina (Nómadas. Critical Journal of Social and Juridical Science, 2015)
The purpose of this paper is to show how the classical concept of war is fading out since Clausewitz times, as the geopolitical panorama was changing. The thesis maintained by the military man and polemology expert Carl Philipp Gottfried von Clausewitz were valid during the Westfalian period, foundering in the XX Century, when a new way to make war begins to arise, that we can describe as asymmetrical. The direct or indirect implementation of the Prussian soldier theories accounts for successes and failures, because neither the History nor the war are linear and teleological processes that can be developed in an office.